Permanent dipole moment of LiCs in the ground state - Deiglmayr, Johannes; Grochola, A.; Repp, M.; Dulieu, O.; Wester, R.; Weidemüller, Matthias (Physical review. A, Atomic, molecular, and optical physics, 2010)
Recently we demonstrated the formation of ultracold polar LiCs molecules in deeply bound levels of the X1Σ+ ground state, including the rovibrational ground state [J. Deiglmayr et al., Phys. Rev. Lett. 101, 133004 (2008)]. Here we report on an experimental determination of the permanent electric dipole moment of deeply bound LiCs molecules. For X1Σ+, v′′=2, and v′′=3 we measure values of μ=5.5(2) D and 5.3(2) D, respectively.